Volumetric incorporation of NV diamond emitters in nanostructured F2 glass magneto-optical fiber probes. (30th August 2022) - Filipkowski, Adam; Mrózek, Mariusz; Stępniewski, Grzegorz; Kierdaszuk, Jakub; Drabińska, Aneta; Karpate, Tanvi; Głowacki, Maciej; Ficek, Mateusz; Gawlik, Wojciech; Buczyński, Ryszard; Wojciechowski, Adam; Bogdanowicz, Robert; et al.
Abstract: Integration of optically active diamond particles with glass fibers is a powerful method of scaling diamond's magnetic sensing functionality. We propose a novel approach for the integration of diamond particles containing nitrogen-vacancy centers directly into the fiber core. The core is fabricated by stacking the preform from 790 soft glass canes, drawn from a single rod dip-coated with submicron diamond particles suspended in isopropyl alcohol. This enables manual control over the distribution of nanoscale features, here – the diamond particles across the optical fiber core. We verify this by mapping the diamond distribution in the core using confocal microscopy. The particles are separated longitudinally by 12–29 μm, while in the transverse plane a separation of approximately 1.5–2.2 μm is observed, corresponding to the individual cane diameter in the final fiber, and without significant agglomeration. The fiber's magnetic sensitivity is confirmed in optically detected magnetic resonance recorded with a coiled, 60-cm-long fiber sample with readout contrast of 1.3% limited by microwave antenna coverage. Moreover, magnetic-field dependence of the NV ─ fluorescence intensity is demonstrated in the absence of microwaves, allowing magnetometric applications with a large (from 0 to 35 mT) B-field dynamic range. Graphical abstract: Image 1